Cooperation Between Dynamic Coefficient of Restitution and Density Ratio in Supporting Granular Gas Oscillation Occurrence - Sparisoma Viridi (Indonesian Journal of Physics, 2007)
Oscillations in granular gas are observed and experimental results show, that there is a cooperation between dynamics coefficient of restitution and density ratio simultaneously, which decides whether a binary mixture could experience an oscillation or not.